2015
DOI: 10.1075/jhp.16.1.03deg
|View full text |Cite
|
Sign up to set email alerts
|

Grammaticalization or pragmaticalization of discourse markers?

Abstract: Discourse markers are a crucial component of natural language, which is why a description and account of their diachronic evolution must be part of our linguistic models. However, researchers have different views on whether this evolution should be accounted for in terms of grammaticalization and/or pragmaticalization. In this paper, we provide a structured overview of the accounts given for the diachronic evolution of DMs. It is shown that the different positions encountered in the literature can be brought b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(25 citation statements)
references
References 78 publications
0
15
0
10
Order By: Relevance
“…, and tu (< itu). As will be argued below, the monosyllabization of these particles is connected with their "pragmaticalization" (Diewald 2011;Degand and Evers-Vermeul 2015), that is, their acquisition and increase of pragmatic functions besides their grammatical functions.…”
Section: The Malay Examined In This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…, and tu (< itu). As will be argued below, the monosyllabization of these particles is connected with their "pragmaticalization" (Diewald 2011;Degand and Evers-Vermeul 2015), that is, their acquisition and increase of pragmatic functions besides their grammatical functions.…”
Section: The Malay Examined In This Studymentioning
confidence: 99%
“…Recent fieldwork-based studies on this variety include Shoho (2006Shoho ( , 2013, Nomoto (2006aNomoto ( , 2006b, Soh (2011Soh ( , 2015, and Nomoto and Wahab (2012). I assume more scholarship on this topic has been produced at Malaysian universities Simon-Vandenbergen (2006), Maschler and Schiffrin (2015), Degand and Evers-Vermeul (2015), Crible (2017), Fedriani and Sansò (2017), Bayer and Struckmayer (2017). 2 It should also be recalled that grammaticalization by definition leads to decategorialization (Diewald 2011).…”
Section: The Malay Examined In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent decades, the relationship of grammaticalization and pragmaticalization has been in the focus of a number of studies (Barth, Couper-Kuhlen 2002, Traugott, Dasher 2002, Brinton 2010, Diewald 2011, Heine 2013, Degand, Evers-Vermeul 2015. However, less attention has been paid to these phenomena in the development of complex grammatical items, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not contrast the two phenomena, but consider pragmaticalization to be a type of grammaticalization. That is, we consider the development of the pragmatic function as a process of change where the outcome pertains to the level of discourse but follows the main mechanisms of grammaticalization (see Diewald 2011, Traugott 2010, Degand, Evers-Vermeul 2015. It will be demonstrated that the development of nii et has three stages, including (i) the starting point (two adjacent freely combined items located at the clause border); (ii) reanalysis of the source form as a complex conjunction; (iii) the development of a pragmatic marker accompanied by the shift to the left periphery (and eventually to the right periphery).…”
Section: Introductionmentioning
confidence: 99%